2010
DOI: 10.1177/193758671000400104
|View full text |Cite
|
Sign up to set email alerts
|

Application of Space Syntax Theory in the Study of Medical-Surgical Nursing Units in Urban Hospitals

Abstract: Understanding how and when nurses communicate with each other could help designers of healthcare spaces create more effective environments that support nurses' work and personal health and welfare. The findings of this study suggest that further exploration is needed to confirm this theory's application to healthcare environments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
54
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(63 citation statements)
references
References 34 publications
6
54
0
Order By: Relevance
“…However, at Hospital S, the solid partition between the NS and doctors' office prevents nurses from locating doctors; therefore, nurses must go to doctors' office to communicate with doctors, which could increase nurses' walking distance and decrease communication efficiency. The presence and locations of space boundaries, such as walls and partitions, impact the degree of visibility (Johanes & Atmodiwirjo, 2015), which is an important factor that influences communication between nurses and doctors (Becker, 2007;Trzpuc & Martin, 2010).…”
Section: Visibility On Communicationmentioning
confidence: 99%
“…However, at Hospital S, the solid partition between the NS and doctors' office prevents nurses from locating doctors; therefore, nurses must go to doctors' office to communicate with doctors, which could increase nurses' walking distance and decrease communication efficiency. The presence and locations of space boundaries, such as walls and partitions, impact the degree of visibility (Johanes & Atmodiwirjo, 2015), which is an important factor that influences communication between nurses and doctors (Becker, 2007;Trzpuc & Martin, 2010).…”
Section: Visibility On Communicationmentioning
confidence: 99%
“…As a result, the findings of these studies in dealing with the relationships between the network of spaces, on the one hand, and psychological responses and behavior, on the other, are less context-dependent and more generalizable [1,2,3,4,5,6,7,8,9,10,11,12]. Several space syntax studies to date, including the ones reported here, show strong relationships between spatial network measures and environmental behavior and psychology.…”
Section: Introductionmentioning
confidence: 99%
“…In a different kind of study, Trzpuc and Martin [10] used data from semi-structured interviews with end users and the more generic measures of centrality of space syntax to test several hypotheses on the potential functional benefits of visibility and accessibility in three medical-surgical units. They found that nurses’ perception of the potential functional benefits of visibility and accessibility did not match the potential benefits of these units identified using their network centrality values.…”
Section: Introductionmentioning
confidence: 99%
“…At a unit level participants' preference for greater privacy was for units with low integration and high control values; and within any unit, at a bed location level participants' preference for privacy was in lower integration and lower control locations. Finally, Trzpuc & Martin (2010) conducted semi-structured interviews of staff members to test several hypotheses developed based on the centrality of spaces measured using space syntax techniques in three medical-surgical units with different layouts. They found that nurses' perception of the potential functional benefits of visibility and accessibility in the units did not match the potential benefits of these units predicted based on their centrality values.…”
Section: Studies Involving Psychology and Unit Layout Featuresmentioning
confidence: 99%